Incentives for Process Innovations under Discrete Structural Alternatives of Competition Policy - Andrej E. Sastitko; Alexander A. Kurdin (National Research University Higher School of Economics, 2015)
This study analyses the incentives for process innovations under different conditions determined by the competition policy for intellectual property rights (IPR) and particular features of markets and technologies. Competition policy is defined by the presence or absence of compulsory licensing, markets are characterized by technological leadership or technological competition. The results of modelling show that the uncertainty engendered by technological competition may lower the intensity of innovative activities, if there are no mechanisms of coordination between participants. Voluntary licensing generally improves social welfare but does not guarantee an increase in innovative efforts. Compulsory licensing can impede innovations due to the opportunistic behaviour of market participants but certain measures of state policy can prevent this negative effect.
Keywords: L24; O31; K21; 330; competition policy; compulsory licensing; process innovations